Masjid : Sejarah Singkat, Komponen dan Konteks Regional - Effendi Nurzal; FaizaAidina (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
The mosque is a public building and one of the architectural forms of Islamic culture. There have been numerous studies discussing mosques, including historical studies, analyses of stylistic forms, thermal comfort, circulation, and other aspects. Due to the multitude of research variations, this article aims to re-explore the foundational knowledge of mosques. It begins by delving into the origins of mosques and their brief history, the initial mosque prototypes, their relationship with the building's components, and the evolution of their architecture in relation to regional contexts.